RECYCLIZATION OF 3-(2-(MORPHOLINE-4-CARBONYL)PHENYL)-4H-CHROMEN-4-ONES WITH 1,2-N,N- AND 1,3-N,N-BINUCLEOPHILES - Kukushkina, K.V.; Moskvina, V.S. (Reports of the National Academy of Sciences of Ukraine, 2024)
The aim of this study is to investigate the regioselectivity of the recyclization reactions of 3-(2-(morpholine-4-carbonyl) phenyl)-4H-chromen-4-ones with methylhydrazine as 1,2-N,N-binucleophile and guanidine carbonate as 1,3-N,N-binucleophile. As a result of this work, methodologies were developed and adapted to synthesize 3-(2-hydroxyaryl)-1-methyl-1H-pyrazoles and 2-amino-4-(2-hydroxyaryl)pyrimidines in high yields. The synthesized products containing various functional groups such as hydroxyl, carboxyl, carboxamido and amino groups are promising compounds for biological screening and/or further directed structural modification to generate compounds with a wide range of useful properties. In addition, these products have the potential to explore their chelating and fluorescent properties.